Transdermal drug delivery of labetalol hydrochloride: Feasibility and effect of penetration enhancers - Saqib Zafar; Asgar Ali; Mohammed Aqil; Abdul Ahad (Wolters Kluwer Medknow Publications, 2010)
Objectives : The objective of this study is to investigate the feasibility of transdermal drug delivery of Labetalol Hydrochloride (LHCl) and to study the effect of different penetration enhancers on the skin permeability of LHCl. Methods : The permeability experiments were conducted using a horizontal glass diffusion cell with a diffusional area of 2.37 cm-2 on albino rat skin. The effect of various penetration enhancers namely turpentine oil, dimethyl formamide (DMF), menthol, dimethyl sulfoxide, pine oil, and 2-pyrollidone, and the effect of the concentration of drug and enhancer in the donor phase on the skin permeability of LHCl was studied. Results : The apparent partition coefficient of the drug was found to be 6.95, suggesting it to be a lipophilic drug. The preliminary skin permeation studies revealed that the permeation of LHCL through albino rat skin was moderate (Kp = 6.490 Χ 10 -2 cm hr -1 ) from isotonic phosphate buffer of pH 7.4. An appreciable increase in the LHCl permeability coefficient was observed on using a co-solvent (ethanol 95%) with the penetration enhancers in the donor phase. DMSO (10% v/v) was found to be the most effective enhancer for Labetalol hydrochloride (Enhancement Factor = 1.165). An increase in the concentration of drug and enhancer in the donor cell accentuated the permeability coefficient of LHCl. Conclusions : It was concluded that LHCl could be delivered via the dermal route with the use of 10% DMSO as the penetration enhancer.